2018
DOI: 10.1002/admi.201800323
|View full text |Cite
|
Sign up to set email alerts
|

Stable 2D Conductive Ga/Ga(OxHy) Multilayers with Controlled Nanoscale Thickness Prepared from Gallium Droplets with Oxide Skin

Abstract: The practical applicability of ultrathin films, which offer interesting and novel functionalities, is often limited by difficulties in achieving large area deposition while maintaining homogenous layer properties. Herein, a new deposition method allowing ultrathin, conductive gallium‐containing layers to be prepared at ambient conditions on wafer‐scaled areas is presented. Multilayers are formed by repetition of the deposition procedure. High‐resolution structural analysis using X‐ray reflectometry shows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Furthermore, increasing the number of uniform repeat units results in narrowing the peak while the peak intensity increases. However, with films made from Ga, 9 we observed an increase in the peak width with peak order. Furthermore, we found a relative increase in the intensity of the second-order peak with increasing layer number.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Furthermore, increasing the number of uniform repeat units results in narrowing the peak while the peak intensity increases. However, with films made from Ga, 9 we observed an increase in the peak width with peak order. Furthermore, we found a relative increase in the intensity of the second-order peak with increasing layer number.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
“…In a recent publication, we introduced a cost-efficient and environmentally friendly deposition method for ultrathin heterocomposite metal-and metal (hydr)oxide layers. 9 Gallium with a melting temperature of 29.76 °C was employed. 10 This deposition method called induced breakup after forced wetting leads to laterally homogeneous and vertically heterostructured multilayers with a thickness from 2.9 up to 24 nm depending on the number of deposited layers.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the Ga-based liquid metal is exposed to ambient atmosphere, a thin self-limiting oxide layer can spontaneously and rapidly form on the surface. Consequently, it significantly changes the bulk behavior of liquid metal along with its surface tension and wetting [21][22][23] , allowing the liquid metal to adhere to almost any solid surface and providing a new insight to manipulate the liquid-metal structure for specific applications [22,[24][25][26][27] . For example, Khan et al recently reported an approach to tune the interfacial tension of an EGaIn via electrochemical deposition (or removal) of an oxide layer on its surface using external electrical field [22] .…”
Section: Introductionmentioning
confidence: 99%